Whose Castle is it Anyway?: Local/Global Negotiations of a Shakespearean Location - Refskou, Anne Sophie (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
Kronborg Castle in the Danish town of Elsinore is a location strongly associated with Shakespeare thanks to the setting of Hamlet. It is a place where fiction currently eclipses history, at least in the context of a cultural tourist industry where Shakespeare’s name is worth a great deal more than Danish national heritage sites. Indeed, Kronborg is now widely marketed as ‘Hamlet’s Castle’ and the town of Elsinore has acquired the suffix ‘Home of Hamlet’. This article examines the signifiers implied in the naming and renaming of Kronborg as a Shakespearean location, while also looking at its unique international Shakespearean performance tradition, which spans two centuries. It describes how the identity of the castle has been shaped by its Shakespearean connection against the backdrop of changing ideologies in the twentieth and twenty-first centuries, and poses questions as to how this identity may continue to develop within the current contexts of renewed nationalism in Europe and the world.